Disfagia em pacientes neurológicos pós extubação da ventilação mecânica - Werle, Roberta Weber (2016)
PURPOSE: To investigate the presence of dysphagia in patients with neurological dysfunctions after they have been extubated in the Intensive Care Unit (ICU). Secondary objectives were: To evaluate the incidence of factors related to dysphagia in patients under treatment in ICU, as well as to make an analysis of variables like Maximal Inspiratory Pressure, number of days under Mechanical Ventilation (MV), number of days in ICU, use of tracheostomy, Glasgow Coma Scale (GCS) and peak cough flow reflex in neurological patients before extubation. METHODS: Firstly, we made a systematic review considering the Cochrane Handbook guidelines. The following question was considered in the research: What is the incidence and related factors to dysphagia in ICU? The research was performed on the databases of PubMed, ScienceDirect and Scopus. The key words used were: “epidemiology”, “incidence”, “deglutition disorders”, “intensive care units”, “airway extubation”, and “artificial respiration”. After that, we conducted a case-control study at the ICU of a public hospital in the south of Brazil, where 38 neurological patientes were evaluated and divided in a group in which dysphagia was present and in a second group without dysphagia. All patients had been on mechanical ventilation for a period longer than 24 hours and were in the imminence of extubation of the endotracheal tube (ETT) or the removal of the tracheostomy. Before the process of extubation, all patients passed through the tests of the strength of the respiratory musculature, GCS and peak cough flow reflex. Between 24 and 48 hours after the removal of the ETT or the tracheostomy, all patients were submitted to a Speech-Language Pathology evaluation based on the Dysphagia Risk Evaluation Protocol. RESULTS: The incidence of dysphagia varied from 38,1% to 93%. Time of Endotracheal Intubation (EI), MV and sepsis were found to be risk factors for dysphagia. We verified that both the groups with dysphagia and without dysphagia had similar outcomes in tests of the strength of the respiratory musculature, GCS and peak cough flow reflex . Age and time of hospitalization had statistic differences between the two groups. Evaluating the group of patients with neurological dysfunction, regardless the presence of dysphagia, there was a correlation, with statistical significance, among the following variables: Maximal Inspiratory Pressure, peak cough flow reflex, motor response (MR) and number of days under MV. The correlation of the use of tracheostomy, number of days under MV and number of days in ICU also presented statistical significance. CONCLUSION: Through the systematic review, it was possible to identify the wide variability of incidence of dysphagia after extubation. Moreover, time of EI, time of MV and sepsis are the most relevant factors related to the development of oropharynx dysphagia among patients in ICU. The neurological patients with dysphagia have more advanced age and need a longer period of time in hospital. All neurological patients, regardless the presence or absence of dysphagia, the use of tracheostomy is related to a decrease in the necessity of time in ICU. Inspiratory muscular strength is related to the peak cough flow. Furthermore, the good motor response in the GCS is related to fewer days under MV considering neurological patients in ICU.